Sediment fingerprint tracing: unravelling provenance of freshly deposited sediment in the Rhine River - Marcel van der Perk; Jana Cox; Hans Middelkoop (Journal of Soils and Sediments, 2026)
Purpose Quantifying and understanding fine sediment transfers from catchment sources to large river deltas is crucial for effective, integrated river basin management. This study aimed to identify the source areas of fine sediments contemporary deposited along the Rhine River. Methods We sampled fresh fine sediment deposits along the Rhine mainstem after a single minor high-water event in summer 2023, and analysed the element concentrations, on which we performed a principal component analysis (PCA). To calculate the source areas of the event sediments and their downstream transfer, we calibrated a spatial sediment transfer model on the scores of the PC that was interpreted to be primarily controlled by the geogenic composition of the source sediments using auxiliary data on source area geochemistry of the Rhine basin. Results The model calibration results revealed the relative importance of nearby sediment sources over sources further upstream. The relative contribution of the upstream sources of the sediment load of the 2023 summer event dwindled by 0.42% on average per kilometre downstream transport. This implied that although the Swiss part of the Rhine basin upstream from the Aare confluence contributed 64% to the 2023 event discharge, it contributed for only 25% to the total sediment load to the Rhine delta. Conclusion The pursued sediment fingerprint tracing approach provides meaningful insights in the provenance of the freshly deposited 2023 event sediments and the role of river channels and banks as temporary sources and sinks of fine sediments. These components remain undetected in traditional long-term sediment mass budgets of rivers but are essential for a proper understanding of the transfer of fine sediments and associated contaminants at the river basin scale.

Dramatically suppressed climate signals in the Yellow River - Yonggui Yu; Rick J. Yang; Gang Wang; Jaap H. Nienhuis; Xianyao Chen; James T. Liu; Marcel van der Perk; Rens van Beek; Xuefa Shi; Shuqing Qiao; Zhi Li; Jay Lee; et al. (Global and Planetary Change, 2025)

Inefficient burial of terrestrial organic carbon in deltas - Yonggui Yu; Jaap H. Nienhuis; Zhengquan Yao; Marcel van der Perk; Bin Zhao; Shuqing Qiao; Xuefa Shi; Gabriel Cardenas-Belleza; Sheng Fu; Francien Peterse; Yazhi Bai; Hans Middelkoop (Earth and Planetary Science Letters, 2024)

Correction to: Compositional dynamics of suspended sediment in the Rhine River: sources and controls - Marcel van der Perk; Alvaro Espinoza Vilches (Journal of Soils and Sediments, 2020)

Compositional dynamics of suspended sediment in the Rhine River: sources and controls - Marcel van der Perk; Alvaro Espinoza Vilches (Journal of Soils and Sediments, 2020)
Purpose Information on the geochemical composition of suspended sediments in rivers is crucial to identify sediment source type or area. In large river basins, however, the relation between sediment composition and its controlling factors is often obscured. This study aims to assess and improve the conceptual understanding on the factors and mechanisms that control the composition of suspended sediments in the River Rhine, one of the large European rivers, and to identify the dominant source types of elements. Materials and methods We performed log-linear regression analysis and principal component analysis (PCA) on bi-weekly monitoring data of suspended sediment composition, supplemented with daily measurements of suspended sediment concentrations (SSC) and discharge at the Lobith monitoring station near the German-Dutch border for the period 2011–2016. Results and discussion The statistical analyses show a consistent grouping of elements that display contrasting temporal variation or different responses to increased discharge. The contrasting behaviour also becomes manifest in the results from the PCA. A first component that explains about the half of the total variance in the entire dataset reflects the variation in clay content in the suspended sediment. A second component reflects anthropogenic pollution and explains about a quarter of the total variance. A third component probably reflects variation in sediment provenance. Conclusions The majority of the temporal variation in suspended sediment composition can be attributed to variations in grain size (clay content), organic matter content, and anthropogenic pollution. Only a minority of the variation can be attributed to variations in the contributions from different upstream source areas. This variation represented by the third and higher components from the PCA can potentially be used for sediment provenance analysis.

Pathways of Water and Sediment in the Biesbosch Freshwater Tidal Wetland - Eveline C. van der Deijl; Marcel van der Perk; Hans Middelkoop (Wetlands, 2019)

Preface - José Andrés López-Tarazón; Patrick Byrne; Marcel van der Perk (Journal of Soils and Sediments, 2017)

Factors controlling sediment trapping in two freshwater tidal wetlands in the Biesbosch area, The Netherlands - Eveline C. van der Deijl; Marcel van der Perk; Hans Middelkoop (Journal of Soils and Sediments, 2017)

The Impact of Climate Change on Metal Transport in a Lowland Catchment - René R. Wijngaard; Marcel van der Perk; Bas van der Grift; Ton C. M. de Nijs; Marc F. P. Bierkens (Water, Air, & Soil Pollution, 2017)

Sediment response to catchment disturbances - Philip N. Owens; Ellen L. Petticrew; Marcel van der Perk (Journal of Soils and Sediments, 2010)

The Rhine delta—a record of sediment trapping over time scales from millennia to decades - Hans Middelkoop; Gilles Erkens; Marcel van der Perk (Journal of Soils and Sediments, 2010)

Sediment management and the renewability of floodplain clay for structural ceramics - Michiel J. van der Meulen; Ane P. Wiersma; Marcel van der Perk; Hans Middelkoop; Noortje Hobo (Journal of Soils and Sediments, 2009)

Changes in Nutrient Emissions, Fluxes and Retention in a North-Eastern European Lowland Drainage Basin - Daniel S. J. Mourad; Marcel Van Der Perk; Kristjan Piirimäe (Environmental Monitoring and Assessment, 2006)

Environmental Mobility of Radiocaesium in the Pripyat Catchment, Ukraine/Belarus - Peter A. Burrough; Marcel van der Perk; Brenda J. Howard; Boris S. Prister; Umberto Sansone; Oleg V. Voitsekhovitch (Water, Air, & Soil Pollution, 1999)

Variation in composition of stream bed sediments in a small watercourse - Marcel Van der Perk; Pauline F. M. Van Gaans (Water, Air, & Soil Pollution, 1997)

VARIATION IN COMPOSITION OF STREAM BED SEDIMENTS IN A SMALL WATERCOURSE - MARCEL VAN DER PERK; PAULINE F. M. VAN GAANS (Water, Air, & Soil Pollution, 1997)